O desafio da educação para a cidadania global no contexto das práticas do ensino de/por meio da língua inglesa - Caldas, Adriane Balzaretti (Universidade do Vale do Rio dos Sinos, 2022)
Mobilizing for social transformation, creating global and local bridges, from the perspective of interculturalism, integrated curriculum and meaningful and contextualized experiences in teaching and learning practices in additional language classes can contribute significantly to the formation of critical and reflective global citizens. Therefore, this study aimed to verify to what extent, practices of a critical and reflective approach to education for global citizenship are adopted in the Teaching of Middle and High School English Language. The investigation focused on conceptions of the critical approach to education for global citizenship, intercultural citizenship, content and language integrated learning and the reflective teacher. A methodological path of teaching practices observation and analysis experienced by a group of Middle and High school English teachers was carried out at Colégio Anchieta. The focus group technique was adopted so that the intended final proposal for the research was built in a dialogic way between the researcher and the English teachers. Among the findings that approach the objective of this study, the innovative proposals for integrated learning and interdisciplinary projects, as well as the use of varied materials and resources that stimulate reflective practices, are evident. However, it appears that the number of practices that develop skills such as self-knowledge, self-regulation and self-assessment is insufficient. In this regard, considering the gap which relates to the investigated approach, there is an absence of moments that promote more time for active listening and discussion among teachers from different areas of knowledge that could result in the integrated planning qualification. As an intervention proposal, a set of indicators was presented for the evaluation of practices, and finally recommendations were suggested to qualify the pedagogical practice in activities that involve the teaching of English Language, aiming at integrative planning, teacher training and practices of the critical and reflective approach for global citizenship education.
Keywords: Cidadania global; Currículo bilíngue integrado; Prática crítico-reflexiva; Educação básica; Gestão educacional; Global citizenship; Integrated bilingual curriculum; Critical-reflective practice; Basic education; Educational management; ACCNPQ::Ciências Humanas::Educação